1987
DOI: 10.1164/ajrccm/136.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Makes Airway and Early Parenchymal Asbestos-Induced Lung Disease Worse in the Guinea Pig

Abstract: In order to assess the effects of cigarette smoke and asbestos exposure, we divided guinea pigs into 4 groups: smoking or nonsmoking, and asbestos-exposed or not asbestos-exposed groups. Asbestos-exposed animals were given a single intratracheal instillation of 5 mg UICC amosite, a dose and method of administration that we have previously shown produces morphologic changes in the small airways as well as minimal interstitial fibrosis. Animals were smoked 5 days per week for 6 months. By itself, smoking did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Smoking produces lesions similar in location and appearance [pigmentation, inflammation, and fibrosis of the walls of the membranous and to a certain extent the RB (Wright et al 1992)] to those caused by dusts, although smoke-induced lesions tend to be more proximal in the bronchioles and dust-induced lesions more distal. Synergistic interactions between smoke and dust may amplify dust effects as indicated in animal models (Tron et al 1987); thus, determining what effects really are chronic ambient PM effects is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking produces lesions similar in location and appearance [pigmentation, inflammation, and fibrosis of the walls of the membranous and to a certain extent the RB (Wright et al 1992)] to those caused by dusts, although smoke-induced lesions tend to be more proximal in the bronchioles and dust-induced lesions more distal. Synergistic interactions between smoke and dust may amplify dust effects as indicated in animal models (Tron et al 1987); thus, determining what effects really are chronic ambient PM effects is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…We have discussed elsewhere [2] the significance of our observation that asbestos, either alone or with cigarette smoke, produces enlarged airspaces (i.e., emphysema [27]) in this model, and we suggested that the process may be related to chronic low-grade inflammation with release of proteolytic enzymes, in much the same way as smoke is thought to produce emphysema. Inorganic dusts are traditionally associated with fibrotic reactions and restrictive functional profiles, but Becklake [28] recently reviewed the epidemiologic data on airflow obstruction in workers with occupational exposure to a variety of inorganic agents and concluded that workers with many types of dust exposure appear to have evidence of airflow obstruction (structural basis unknown) even in the absence of smoking.…”
Section: Discussionmentioning
confidence: 85%
“…Table 2 shows a series of corelations generated using the morphological data [2] and functional data from these animals. There is a strong positive correlation between increases in wall thickness of respiratory bronchioles or alveolar size and increases in FRC and RV, as well as a strong and consistently negative correlation between increases in wall thickness and the measurements of flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations